Social and Environmental Impact of the Community Rangers Program in Aceh - Paler, Laura (World Bank, Washington, DC, 2016)
This report presents the results of a randomized evaluation larger pool of 452 eligible candidates within the 14 CRP of the impact of the Community Rangers Program 'treatment' communities, 280 such youths were randomly (CRP), a community-based forest protection program selected to serve as rangers and 172 were assigned to a implemented in Aceh, Indonesia, in 2011-14. Fauna and control group. Additional observational analysis and data Flora International (FFt) implemented the CRP with funding collected in the non-CRP treatment Leuser National Park from the Consolidating Peaceful Development in Aceh addresses potential spillover concerns. The evaluation (CPDA) Trust Fund of the World Bank. The evaluation was employs data from individual, household, and villageunderMtaken by a team of independent researchers based head surveys, as well as ground-sourced environmental at universities in the United States.